2019
DOI: 10.5194/acp-19-6107-2019
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous sulfate aerosol formation mechanisms during wintertime Chinese haze events: air quality model assessment using observations of sulfate oxygen isotopes in Beijing

Abstract: Abstract. Air quality models have not been able to reproduce the magnitude of the observed concentrations of fine particulate matter (PM2.5) during wintertime Chinese haze events. The discrepancy has been at least partly attributed to low biases in modeled sulfate production rates, due to the lack of heterogeneous sulfate production on aerosols in the models. In this study, we explicitly implement four heterogeneous sulfate formation mechanisms into a regional chemical transport model, in addition to gas-phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
211
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(244 citation statements)
references
References 106 publications
22
211
1
1
Order By: Relevance
“…The formation of secondary organic aerosol material in atmospheric aerosols via multiphase processes is strongly related to the acidity. Many atmospheric organic accretion reactions, such as aldol condensation (Noziere and Esteve, 2007;Noziere et al, 2010;Sareen et al, 2010;Li et al, 2011), hemiacetal and acetal formation (Jang et al, 2002;Kalberer et al, 2004;Shapiro et al, 2009;Loeffler et al, 2006), and esterification of carboxylic acids (Barsanti and Pankow, 2006), are acid catalyzed. The acid-catalyzed reactive uptake of epoxide species, especially isoprene epoxydiols (IEPOX) (Paulot et al, 2009;Surratt et al, 2010), to aerosol water has also emerged as a significant source of secondary organic aerosol material Marais et al, 2016;Pye et al, 2013).…”
Section: Interactions Of Aerosol and Cloud Chemistry With Aciditymentioning
confidence: 99%
“…The formation of secondary organic aerosol material in atmospheric aerosols via multiphase processes is strongly related to the acidity. Many atmospheric organic accretion reactions, such as aldol condensation (Noziere and Esteve, 2007;Noziere et al, 2010;Sareen et al, 2010;Li et al, 2011), hemiacetal and acetal formation (Jang et al, 2002;Kalberer et al, 2004;Shapiro et al, 2009;Loeffler et al, 2006), and esterification of carboxylic acids (Barsanti and Pankow, 2006), are acid catalyzed. The acid-catalyzed reactive uptake of epoxide species, especially isoprene epoxydiols (IEPOX) (Paulot et al, 2009;Surratt et al, 2010), to aerosol water has also emerged as a significant source of secondary organic aerosol material Marais et al, 2016;Pye et al, 2013).…”
Section: Interactions Of Aerosol and Cloud Chemistry With Aciditymentioning
confidence: 99%
“…The GEOS-FP datasets are available at a native horizontal resolution of 0.25 • latitude by 0.3125 • longitude, a temporal resolution of 1 h for surface variables, and boundary layer height and 3 h for others. We use the nested-grid version of GEOS-Chem that has 0.25 • × 0.3125 • horizontal resolution over East Asia (70-140 • E, 15-55 • N) (Chen et al, 2009;Zhang et al, 2016;Shao et al, 2019), with boundary conditions archived from the global simulation at 2 • latitude × 2.5 • longitude resolution.…”
Section: Model Descriptionmentioning
confidence: 99%
“…1). The datasets have been widely used to examine urban air quality issues over China in recent studies Li et al, 2017b;Gao et al, 2018;Shen et al, 2019;Li et al, 2019). Quality controls to remove unreliable hourly observations are applied following our previous work .…”
mentioning
confidence: 99%
“…In addition to the RH bias, works that explored the systematic bias between modeled and observed AOD values also suggested that the error within the emission used (Park et al, 2011) or the lack of a nitrate process (Li et al, 2016) may be the reason. GOCART also lacks processes concerning secondary organic aerosols and heterogeneous sulfate formation (Shao et al, 2019). The absence of such processes would bring underestimation of the portion of secondary aerosols which are rather efficient in extinction.…”
Section: 1029/2019jd031465mentioning
confidence: 99%